IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN KINERJA PELAYANAN SURAT IZIN PERDAGANGAN (SIUP) (Studi Pada Kantor Kecamatan Tiris Kabupaten Probolinggo) - Siti Marwiyah; Renny Puspitarini; Abdur Rahman Sholeh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
Problems with public services still often occur, many abuses are committed by the government, starting from the regional to village levels. The lack of implementation and knowledge of good governance makes the public service bureaucracy a bad value in the eyes of society. The application of good governance can be used as part of an effort to implement democratic principles in public services, in view of the current situation of public services that need to be applied regarding good governance in order to achieve good organizational goals, in achieving these goals it is necessary to be supported by human resources. namely employees have the attitude of the principle of good governance. This paper intends to examine the Implementation of the Principles of Good Governance in improving the performance of SIUP servers at the Tiris District Office based on analytical theory according to the United Nations Development Program (UNDP) Sedarmayanti (2012: 5) in Serdamayanti which consists of the Principles of Accountability and the Principle of Transparency, the principle openness and the principle of legal certainty. This study used descriptive qualitative method. The selection of informants was deliberately selected who were considered to understand the matter to be studied, taking data from sources deemed relevant according to the issues and themes raised, so as to produce reliable data and determine the accuracy of research results. The results of this study indicate that the application of the principles of good governance namely Accountability, Transparency, Openness, and Legal Supremacy of the Bureaucratic Apparatus indicates that it has been quite effective and carried out optimally in improving the performance of public service apparatus, especially in serving trade permits at the Tiris District Office.